Suicide warning signs of self-identification in patients with mood disorders: a qualitative analysis based on safety planning - Zhang, Honghui; Zhu, Jiaxin; Niu, Lu; Zeng, Meng; Chen, Tengwei; Chen, Yuedong; Hou, Xiaofei; Tao, Haojuan; Ma, Yarong; Lin, Kangguang; Zhou, Liang (Frontiers in Public Health, 2024)
Introduction: Warning signs serve as proximal indicators of suicide risk, making early recognition imperative for effective prevention strategies. This study aimed to explore selfidentified suicide warning signs among Chinese patients with mood disorders based on safety planning framework.Methods: Researchers collaborated with patients to develop a safety plan and compiled warning signs based on it. Word frequency and network analysis were conducted to identify key warning signs. Directed content analysis categorized these signs into cognitive, emotional, behavioral, or physiological themes according to the suicide mode theory. Additionally, we examined potential variations in reported warning signs among participants with different demographic characteristics, including age, gender, and history of suicide attempts.Results: "Low mood" and "crying" emerged as prominent warning signs, with "social withdrawal" closely following. Patients commonly reported emotional themes during suicidal crises, often experiencing two to three themes simultaneously, primarily focusing on emotional, behavioral, and physiological themes. Males exhibited a higher proportion of concurrently reporting three sign themes compared to females (P< 0.05), while no difference was observed in warning signs among patients with other demographic traits.Discussion: This study offers a nuanced understanding of warning signs among mood disorder patients in China.The findings underscore the necessity for comprehensive suicide risk management strategies, emphasizing interventions targeting emotional regulation and social